An Analysis of Reading Material in English Textbook for Eleventh Graders Published by Ministry of Education and Culture (RETAIN, 2020)
ABSTRACT This study is aimed to describe and indentify the reading materials and text genres presented in the English textbook for eleventh graders published by Ministry of Education and culture, in order to know whether they conform to the syllabus of 2013 Curriculum or not in terms of content analysis by BSNP. The data were gained from the reading material presented in the textboook “Bahasa Inggris”. The data were analyzed using the adapted develped checklist from Hartono (2006) and Bloom’s taxonomy. The descriptive qualitative is designed for this study. Based on the results of the study gained, the researcher concludes; 1) there are five reading materials found in the textbook. They conform to the basic competence and indicators of 2013 Curriculum hence, some indicators are unfullfiled yet. 2) there are four text genres found in the textbook, those are; formal invitation, analytical exposition, personal letter, and explanation. They are suitable with the syllabus of 2013 Curriculum. Keywords: Reading Materials, Genre Analysis, Textbook, 2013 Curriculum